Narrativas sobre o (meu) corpo gordo: estudo autoetnográfico rumo a uma psicologia gorda - Fachim, Felipe Luis (2022)
Narratives about (my) fat body is a research that starts from the following compass question: how can the experience of being fat, systematized by fat studies, contribute to the construction of psychological knowledge carried out by and about the fat population? Through an autoethnographic method of phenomenological and hermeneutical inspiration associated with gender studies and fat studies, we sailed through the adipose sea towards a contribution to the field of psychology. Fat Psychology is a proposal to inaugurate a territory of studies, based on fat epistemologies, whose main characteristic is to criticize the tradition of knowledge in psychology that contributed to the construction of the notion of the fat body as a disease and to propose a positive look at life experiences of the Fat Body